2014
DOI: 10.1089/dna.2013.2263
|View full text |Cite|
|
Sign up to set email alerts
|

Correlations of MCP-1 −2518A>G Polymorphism and Serum Levels with Cerebral Infarction Risk: A Meta-Analysis

Abstract: This meta-analysis was performed to evaluate the relationships between the monocyte chemoattractant protein-1 (MCP-1) -2518A>G (rs1024611 A>G) polymorphism and its serum levels, and the risk of cerebral infarction. The PubMed, CISCOM, CINAHL, Web of Science, Google Scholar, EBSCO, Cochrane Library, and CBM databases were searched for relevant articles published before October 1st, 2013 without language restrictions. Meta-analysis was conducted using the STATA 12.0 software. Crude odds ratios (ORs) or standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Acute stroke is a serious complication of cerebral vascular disease with a low occurrence of disability, which has been traditionally defined as NIHSS score with no more than 4. 1,2 According to the increasing number of stroke patients, this disease becomes a severe public health concern owing to the first leading cause of mortality and disability. 3,4 Furthermore, previous evidence have suggested that a number of severe major stroke patients suffer a stroke attack followed by initial minor stroke within the first few hours or days.…”
Section: Introductionmentioning
confidence: 99%
“…Acute stroke is a serious complication of cerebral vascular disease with a low occurrence of disability, which has been traditionally defined as NIHSS score with no more than 4. 1,2 According to the increasing number of stroke patients, this disease becomes a severe public health concern owing to the first leading cause of mortality and disability. 3,4 Furthermore, previous evidence have suggested that a number of severe major stroke patients suffer a stroke attack followed by initial minor stroke within the first few hours or days.…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese subjects, MCP-1 -2518 A/G polymorphism was not associated with CAD risk [ 50 ]. In a previous study, we reported that subjects with A/A genotype exhibited higher MCP-1 levels than other genotypes in Korean elderly, and had higher CVD risk [ 55 ]. These results suggest that MCP-1 concentration and CVD risk vary with MCP-1 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 -2518A > G (rs1024611) and -927G > C (rs3760396) situated in the distal promoter regulatory region of the MCP-1 gene could affect the transcription of MCP-1 [24]. Two recent meta-analysis studies suggested that MCP-1 rs1024611 is associated with ischemic heart disease and ischemic stroke susceptibilities [25, 26]. Furthermore, cerebral infarction patients had higher levels of serum MCP-1 than did healthy control subjects; however, two SNPs, rs1024611 and rs3760396, were not remarkably associated with ischemic stroke, which might have been due to ethnic differences since most significant findings were observed among Caucasian populations [26].…”
Section: Discussionmentioning
confidence: 99%